A domain specific language for the development of collaborative systems - Bibbó, Luis Mariano; Pons, Claudia Fabiana; García, Carlos Diego (2008)
Domain-Specific Languages (DSLs) are high level languages defined for combining expressivity and simplicity by means of constructs which are close to the problem domain and distant from the intricacies of underlying software implementation constraints. This paper presents a language to graphically document the analysis and design decisions embodied in Collaborative System development. The language was designed as a conservative extension of the UML and it enables the application of the MDD approach to the development of such systems.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática-UNLP (Colección BIPA / Biblioteca.) -- Disponible también en línea (Cons. 20/03/2009)
IEEE International Conference of the Chilean Computer Science Society SCCC 2008. Punta Arenas. November 2008. IEEE Press.
Keywords: LENGUAJES DE DOMINIO ESPECÍFICO - DSL; COMPUTACIÓN COLABORATIVA; APLICACIONES COLABORATIVAS